Development of Buccoadhesive Systems of Pentazocine for Systemic Drug Delivery - Sampathkumar, D.; Thilek Kumar, M.; Balasubramaniam, J.; Pandit, J.K. (Osterreichische Apotheker-Verlagsgesellschaft m.b.H.)
Bucoadhesive patches of Pentazocine (PZ) for unidirectional drug delivery were prepared by casting carboxy methyl cellulose (CMC) with glycerol or propylene glycol and CMC-hydroxy ethyl cellulose (HEC) with glycerol. In vitro mucoadhesivity of the prepared patches were determined using a modified mucoadhesive bond strength apparatus using rabbit small intestine mucosa (SIM). Drug release kinetics was evaluated from composite patches, prepared by covering all but one side of the PZ patches with 3M backing material. Biocompatability / buccoadhesion time and in vivo permeation of placebo and PZ loaded patches were determined using a double blind cross over study in healthy human volunteers. Drug release from CMC-glycerol patches and pure HEC patches showed zero order kinetics with diffusional exponent (n) ranging between 0.79 to 1.046, while that from CMC-HEC and CMC-propylene glycol patches showed an apparent zero order release kinetics. The prepared patches were well tolerated by the human volunteers as they did not produce any side effects at the contact surface. The in vitro mucoadhesivity of CMC-propylene glycol patches were significantly lower than CMC-glycerol based patches. The in vivo permeation of selected PZ patches delivered the drug well above the minimum buccal permeation rate, so as to attain effective blood concentration.
Keywords: Buccal patches; Buccoadhesive; In vitro mucoadhesion; Pentazocine